Application of principles from the International < IR > Framework for including sustainability disclosures within South African integrated reports. (2nd January 2021) - Herbert, Shelly; Graham, Mark
Abstract : With the introduction of integrated reporting, organisations are now encouraged to integrate sustainability disclosures within their integrated reports, in addition to traditional sustainability reporting practices. The purpose of this study is to investigate whether the International < IR > Framework (the Framework) led to a change in how South African listed companies included sustainability disclosures in their integrated reports, looking specifically at the degree of integration of sustainability disclosures, the use of sustainability key performance indicators (KPIs), and the materiality and balance of sustainability disclosures included, which are all based on principles in the Framework. Interpretive content analysis is used to compare the integrated reports in 2011, when integrated reporting became mandatory in South Africa, and 2015, when the Framework was adopted. The results show that there was a significant change in the level of integration and materiality of sustainability disclosures, but there was no significant change in the use of KPIs and the balance of disclosures. This study does not seek to measure the quality of the sustainability disclosures included in the integrated reports beyond the level of the application of Framework principles. This study provides unique insight into how South African companies adapted their sustainability disclosures within their integrated reports in response to the Framework.